Evaluation the effectiveness of implementation of Law No. 12/ 2006 concerning Citizenship - Wiraganti, Risna Wendy; Fatmawati, Yuliana; Amelia, Lia; Hakim, Luqman; Putera, M. Luhtfi Setiarno (Innovative: Journal Of Social Science Research, 2024)
This study examines the concept of citizenship, defining the legal relationship between individuals and the state, encompassing the rights and obligations of citizens. Citizenship in Indonesia is regulated through various principles such as ius sanguinis, ius soli, ius connubii, and naturalization, accommodating different scenarios for acquiring citizenship. According to Law No. 12 of 2006, the regulation of citizenship aims to protect citizens' rights and ensure clear citizenship status. However, the implementation of this law is often hindered by complex and inefficient bureaucratic obstacles. This research employs a normative legal method through literature review, identifying the history of the law's formation and the challenges in its application. Bureaucratic reforms that simplify procedures, enhance inter-agency coordination, and leverage information technology are expected to improve the effectiveness of the citizenship law's implementation, strengthen public trust, and support more harmonious social integration in Indonesia.